Characterization and Transcript Expression Analyses of Atlantic Cod Viperin - Eslamloo, Khalil; Ghorbani, Atefeh; Xue, Xi; Inkpen, Sabrina M.; Larijani, Mani; Rise, Matthew L. (Frontiers in Immunology, 2019)
Viperin is a key antiviral effector in immune responses of vertebrates including the Atlantic cod (Gadus morhua). Using cloning, sequencing and gene expression analyses, we characterised the Atlantic cod viperin at the nucleotide and hypothetical amino acid levels, and its regulating factors were investigated. Atlantic cod viperin cDNA is 1342 bp long, and its predicted protein contains 347 amino acids. Using in silico analyses, we showed that Atlantic cod viperin is composed of 5 exons, as in other vertebrate orthologues. In addition, the radical SAM domain and C-terminal sequences of the predicted Viperin protein are highly conserved among various species. As expected, Atlantic cod Viperin was most closely related to other teleost orthologues. Using computational modelling, we show that the Atlantic cod Viperin forms similar overall protein architecture compared to mammalian Viperins. qPCR revealed that viperin is a weakly expressed transcript during embryonic development of Atlantic cod. In adults, the highest constitutive expression of viperin transcript was found in blood compared with 18 other tissues. Using isolated macrophages and synthetic dsRNA (pIC) stimulation, we tested various immune inhibitors to determine the possible regulating pathways of Atlantic cod viperin. Atlantic cod viperin showed a comparable pIC induction to other well-known antiviral genes (e.g. interferon gamma and interferon-stimulated gene 15-1) in response to various immune inhibitors. The pIC induction of Atlantic cod viperin was significantly inhibited with 2-Aminopurine, Chloroquine, SB202190, and Ruxolitinib. Therefore, endosomal-TLR-mediated pIC recognition and signal transducers (i.e. PKR and p38 MAPK) downstream of the TLR-dependent pathway may activate the gene expression response of Atlantic cod viperin. Also, these results suggest that antiviral responses of Atlantic cod viperin may be transcriptionally regulated through the interferon-activated pathway.